Sodium bicarbonate improves 4 km time trial cycling performance when individualised to time to peak blood bicarbonate in trained male cyclists - Gough, L. A.; Deb, S. K.; Sparks, S. A.; McNaughton, L. R. (Journal of Sports Sciences, 2018)
The aim of this study was to investigate the effects of sodium bicarbonate (NaHCO3) on 4 km cycling time trial (TT) performance when individualised to a predetermined time to peak blood bicarbonate (HCO3-). Eleven male trained cyclists volunteered for this study (height 1.82 ± 0.80 m, body mass (BM) 86.4 ± 12.9 kg, age 32 ± 9 years, peak power output (PPO) 382 ± 22 W). Two trials were initially conducted to identify time to peak HCO3- following both 0.2 g.kg-1 BM (SBC2) and 0.3 g.kg-1 BM (SBC3) NaHCO3. Thereafter, on three separate occasions using a randomised, double-blind, crossover design, participants completed a 4 km TT following ingestion of either SBC2, SBC3, or a taste-matched placebo (PLA) containing 0.07 g.kg-1 BM sodium chloride (NaCl) at the predetermined individual time to peak HCO3-. Both SBC2 (-8.3 ± 3.5 s; p < 0.001, d = 0.64) and SBC3 (-8.6 ± 5.4 s; p = 0.003, d = 0.66) reduced the time to complete the 4 km TT, with no difference between SBC conditions (mean difference = 0.2 ± 0.2 s; p = 0.87, d = 0.02). These findings suggest trained cyclists may benefit from individualising NaHCO3 ingestion to time to peak HCO3- to enhance 4 km TT performance.